The Collective Manager: Group Psychodynamic in Companies Managed by Workers – A Case Study - Meira, Fabio Bittencourt (Organizações & Sociedade, 2014)
This paper summarizes the results of a research on Companies Assumed by Workers (CAW) – firms that go into bankruptcy and end up managed by ex-employees. The main question is how do the workers recreate bonds, social interactions and inherited management practices? The answer is based on group Psychosociology to propose a theoretical construct named collective manager: a reference to the ensemble of group subjective mechanisms that operate throughout their self-organizing process. This construct is presented in a case study, in which theoretical considerations dialog with the field research findings. The outcomes strengthen the understanding that group self-organizing is correlated to the group subjective work of self-limitation. In the case of CAW, the process seems to be leaded by the selective and permanent adjustment of group creative and transformative praxis to environmental constraints and contradictions.